Case Report: Management of recurrent UTI with tigecycline in a kidney transplant recipient - Shettar, Supreeta R.; Sumana, Mahadevaiah Neelambike; Shetty, Manjunath S.; Maheshwarappa, Yogeesh D.; Reddy, Raghukanth G.; Srinivasan, Asha; P, Vamshi Dharan; Kalyatanda, Gautam; S C, Shruthi Shree (Frontiers in Transplantation, 2025)
This case report describes a 37-year-old man who underwent renal transplantation and subsequently developed complicated recurrent urinary tract infections (UTIs) caused by multidrug-resistant (MDR) Klebsiella pneumoniae. Despite initial treatment with fosfomycin and meropenem, the patient experienced persistent UTIs, leading to multiple hospitalizations. The management of these recurrent infections eventually required the use of tigecycline. Although tigecycline is not typically considered a urinary antibiotic owing to its limited urinary excretion, it was successfully employed in this case to manage the recurrent infections. The patient was treated with tigecycline for several episodes of UTI, which provided a crucial therapeutic option in the context of antibiotic resistance. This case underscores the challenges of managing recurrent MDR UTIs in immunocompromised patients and highlights tigecycline as an effective treatment strategy when standard therapies fail.